Explantation of 10 kHz Spinal Cord Stimulation Devices: A Retrospective Review of 744 Patients Followed for at Least 12 Months. Issue 3 (19th January 2021) - Hagedorn, Jonathan M.; Lam, Christopher M.; D'Souza, Ryan S.; Sayed, Dawood; Bendel, Markus A.; Ha, Chris Thuc; Romero, Joshua; Hall, Morgan; Freeman, Eric; Richardson, Brian F.; Hoelzer, Bryan C.
Abstract: Objectives: High‐frequency 10 kHz spinal cord stimulation (10 kHz‐SCS) has achieved analgesia superior to traditional SCS in a number of studies. However, there is concern regarding long‐term outcomes of 10 kHz‐SCS. Prior work has suggested that explant rates are higher with 10 kHz‐SCS. Our primary objective was to determine the explant rate of 10 kHz‐SCS in a large patient cohort from multiple centers followed for at least 12 months after implant surgery. Materials and Methods: We performed a retrospective chart review of all patients who received a 10 kHz‐SCS implant before July 1, 2019. We abstracted patient demographics, implant date, primary site of pain, implant indication, explant date, and reason for explant. A total of 744 patients were included in the study analysis. Results: Average age of the overall cohort was 65.53 years and 407 (54.7%) were women. Average follow‐up for all patients was 793 days. There were a total of 76 explants (10.2%). The most common reason for explant was loss of efficacy, which accounted for 39 explants (51.3% of total explants, 5.2% of overall cohort). Female sex and radiculopathy as the SCS indication were associated with statistically significant decreased risk of 10 kHz‐SCS explant. Conclusions: We found 10 kHz‐SCS explant rates to be similar to prior reported explant rates for traditional SCS devices. Patient‐related factors including female sex and radiculopathy as the primary SCS indication may be protective factors against explantation.